2017
DOI: 10.1101/cshperspect.a027060
|View full text |Cite
|
Sign up to set email alerts
|

Order Matters: The Order of Somatic Mutations Influences Cancer Evolution

Abstract: Cancers evolve as a consequence of multiple somatic lesions, with competition between subclones and sequential subclonal evolution. Some driver mutations arise either early or late in the evolution of different individual tumours, suggesting that the final malignant properties of a subclone reflect the sum of mutations acquired rather than the order in which they arose. However, very little is known about the cellular consequences of altering the order in which mutations are acquired. Recent studies of human m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 64 publications
0
53
0
Order By: Relevance
“…These "driver" mutations are often tissue-specific, suggesting context-dependency as in the case of APC mutations in gastrointestinal tumors (Fearon and Vogelstein 1990;Horii et al 1992;Nakatsuru et al 1992) and DNMT3 in leukemias (Shlush et al 2014). Nonetheless, multiple driver mutations (and clonal expansions) are typically required to initiate a cancer (Vogelstein and Kinzler 2015) and several studies have suggested that the order of mutations influences the phenotype of tumor initiating cells and may be associated with different clinical outcomes (Weaver et al 2014;Ortmann et al 2015; see also Kent and Green 2017).…”
Section: Pretumor Progression and Factors Influencing Clonal Expansionsmentioning
confidence: 99%
“…These "driver" mutations are often tissue-specific, suggesting context-dependency as in the case of APC mutations in gastrointestinal tumors (Fearon and Vogelstein 1990;Horii et al 1992;Nakatsuru et al 1992) and DNMT3 in leukemias (Shlush et al 2014). Nonetheless, multiple driver mutations (and clonal expansions) are typically required to initiate a cancer (Vogelstein and Kinzler 2015) and several studies have suggested that the order of mutations influences the phenotype of tumor initiating cells and may be associated with different clinical outcomes (Weaver et al 2014;Ortmann et al 2015; see also Kent and Green 2017).…”
Section: Pretumor Progression and Factors Influencing Clonal Expansionsmentioning
confidence: 99%
“…Here, again, a number of different truncal or initiating mutations could promote clonal expansion of stem or progenitor cells, but two genes, TP53 and NOTCH1, were the most common truncal mutations.A rather dramatic impact upon clinical features, the responses to therapy, the biology of stem and progenitor cells, and even clonal evolution, has also been observed in myeloproliferative neoplasms, depending on whether a mutation in TET2 occurs before a mutation in JAK2 or vice versa. Rather clearly, the order in which these two mutations occur influences the evolution and even the optimal treatment of these tumors (Ortmann et al, 2015;Kent and Green, 2017). When the genetic (JAK2) or the epigenetic (TET2) mutation is the initial truncal mutation, they each have very different impacts upon the gene expression of the progenitor cell, so that the second mutation results in quite different properties of the cancer.…”
mentioning
confidence: 99%
“…As explained in Methods section, we note that a total of 1000 initial-states were randomly generated to compute the mutation-sensitivity and the orderspecificity values in Eqs. (1) and (2) in all simulations. In addition, we constructed a set of ordered gene pairs to be investigated, Ω, for tractable simulation.…”
Section: Resultsmentioning
confidence: 89%
“…For example, the double mutation in the order of TP53 and NOTCH, which are representative tumorsuppressor and oncogenes, respectively, was frequently observed in early stage of esophageal carcinoma patients [53], whereas the reverse-ordered mutation is likely to lead to a metastasis progression in mouse experiments [63,64]. It was also shown that alteration of RAS, which is another oncogene, before loss of P53 formed a malignant tumor with metastatic behavior, but the reverseordered mutation resulted in benign tumors [2,65].…”
Section: Analysis Of Tumor Suppressor and Oncogenes With Respect To Omentioning
confidence: 99%
See 1 more Smart Citation